Analisis Determinan Kualitas Pelaporan Keuangan Perusahaan Non Jasa Keuangan di Bursa Efek Indonesia - Rahma Purnama Sari; Zikra Supri; Riyanti Riyanti (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The purpose of this research is to analyze the determinants that affect a financial reporting that includes the board of commissioners and audit committee using the IBM SPSS Program in analyzing secondary data. Non-financial service companies in the 2018-2020 period are the samples used in this study. The research method used in this study is a quantitative description with regression analysis. The results of this research test are based on decision making which shows that the audit committee has an influence on the quality of financial reporting, but the audit committee has a not so significant influence on the quality of financial reporting in improving the quality of financial reports, while the test results from research on the board of commissioners are based decision making which shows different results from the audit committee that on the board of commissioners has an influence on the quality of financial reporting. So if the number of commissioners in a company increases, it will affect the quality of financial reporting and the delivery of financial reports to users will be faster and more relevant.